Public’s Knowledge of Heart Failure and its Associated Factors: A Cross-Sectional Study - Fatima Afzal; Sherjeel Adnan; Muhammad Saad; Abeera Saleem; Khush Bakhat; Mehwish Shabbir; Hajrah Mehmood; Rohma Babar; Farwa Ashraf; Huzaifa Ahmed Khan (Dialogue Social Science Review (DSSR), 2025)
Heart failure (HF) is a major global health concern, with increasing prevalence in low- and middle-income nations like Pakistan. Understanding the general population's knowledge and awareness of Heart Failure is essential for developing effective prevention and care strategies. A cross-sectional study was conducted using a standardized questionnaire. The questionnaire covered demographic details, awareness of HF symptoms, risk factors, and preventive strategies. Data were collected from 400 randomly selected participants representing varied socioeconomic backgrounds. The study revealed that 85% of participants had a basic understanding of heart failure. Awareness of key risk factors, including hypertension, diabetes, and smoking, was also low, with only 46% correctly identifying them. Educational interventions were found to improve awareness levels significantly. There is a substantial gap in the knowledge and awareness of heart failure among the general population in District Sialkot. Targeted educational initiatives are urgently required to enhance public understanding of HF symptoms, risk factors, and preventive measures to mitigate the disease's burden.